Design of GH4169 diaphragm for combined improvements of yield strength and surface roughness. Issue 1 (24th February 2023) - Wang, Qiushi; He, Guangli; Zhao, Wenjing; Han, Zhihua; Wei, Linlin
Abstract: Diaphragm compressors have become the primary source of on-site hydrogen compression for hydrogen fuelling stations around the world. The most common hydrogen-compressor-failure mechanism has been identified as diaphragm fracture due to low tensile strength and poor surface properties. In this study, a new type of GH4169 diaphragm with high yield strength and low surface roughness was fabricated. Microstructures, tensile behaviours and surface properties of the specimens were characterized by using scanning electron microscopy, an electronic universal testing machine and atomic force microscopy, respectively. The evolution of the γ ′ ′ and γ ′ phases with temperature has been examined. Both γ ′ ′ and γ ′ phases were precipitant-strengthened phases for GH4169 and the volume and size of γ ′ ′ and γ ′ phases increase with ageing time. In addition, the γ ′ ′ phase is the main strengthening phase and γ ′ is the supportive strengthening phase. Tensile strength was increased due to the strengthening phases at the cost of ductility. The roughness of the diaphragm could reach an arithmetic average roughness (Ra) of 0.1 μ m by applying a cooling-assisted polishing process. This work improves the reliability and reduces the auxiliary steps and down-time for diaphragm compressors. Abstract : A new type of diaphragm with high yield strength and low surface roughness was fabricated for use in hydrogen compressors. Microstructures, tensile behaviours and surface properties of the specimens were characterized by using scanning electron microscopy, an electronic universal testing machine and atomic force microscopy. Graphical Abstract: